'Welcome Home, Our Bitter Home!': Rethinking National Identity in Nuruddin Farah's "Links" - TURAN, AYŞEGÜL (New Bulgarian Univ Sofia, Bulgari, 2024)
Nuruddin Farah's Links (2005) represents the civil war-torn Somalia, and particularly Mogadiscio, from the perspective of Jeebleh, who returns to his homeland after twenty years. The novel, through Jeebleh's exilic perspective, interrogates the implications of national identity and sense of collective belonging in a society driven by clan politics. This article examines the representation of fragmented nationhood as a consequence of the civil war along with the narrative's portrayal of other forms of belonging and collectivity to engender an alternative understanding of national identity. I contend that Links, while maintaining its focus on the national space and what the nation stands for in times of crisis, also offers ways to envision connections between the national space and what lies beyond through the implementation of exilic point of view and literary and non-literary allusions.
Note: This article is produced from my PhD thesis, submitted to the Committee on Comparative Literature, Washington University in St. Louis in 2015. Parts of the text also appeared in the conference presentation given at "Revolutions in Reading: Literary Practice in Transition" organized by Stockholm University in 2021.
Keywords: National Identity; Nation; Exile; Nuruddin Farah; Somalia